2001
DOI: 10.1159/000050485
|View full text |Cite
|
Sign up to set email alerts
|

Usual Interstitial Pneumonia: Idiopathic Pulmonary Fibrosis versus Collagen Vascular Diseases

Abstract: Background: Bronchoalveolar lavage fluid (BALF) lymphocytosis was found in patients with usual interstitial pneumonia (UIP) associated with collagen vascular diseases (CVD) other than diffuse systemic sclerosis (SSc), but it was not found in patients with idiopathic pulmonary fibrosis (IPF), a disease histologically diagnosed as UIP. This difference could be partly due to variations of UIP spectrums between IPF and interstitial pneumonia associated with CVD. Methods: We scored histopathological findings of lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 18 publications
1
18
1
1
Order By: Relevance
“…However, multiple investigations also demonstrate mononuclear collections (including activated effector T cells) are unmistakably present in IPF lungs (1, 26, 27, 36 -39). Moreover, similar or even lesser degrees of T cell infiltration are frequently noted in other adaptive immune diseases, including lung allograft rejection (40) and various autoimmune syndromes (1,36,37,(41)(42)(43)(44), particularly in late fibrotic stages.…”
Section: Discussionmentioning
confidence: 90%
“…However, multiple investigations also demonstrate mononuclear collections (including activated effector T cells) are unmistakably present in IPF lungs (1, 26, 27, 36 -39). Moreover, similar or even lesser degrees of T cell infiltration are frequently noted in other adaptive immune diseases, including lung allograft rejection (40) and various autoimmune syndromes (1,36,37,(41)(42)(43)(44), particularly in late fibrotic stages.…”
Section: Discussionmentioning
confidence: 90%
“…However, with the use of finer classified scores we seemed to lose improved simplicity and reliability in the assessment of the FS and GGS. It is conceivable that the ground-glass opacities do not always represent cellular inflammation in the IPF population [32]. Nagao et al [32 ]demonstrated that the UIP histology showed a greater paucity of bronchoalveolar lavage fluid lymphocytosis in the IPF patient group than in the UIP patient group with associated collagen vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that the ground-glass opacities do not always represent cellular inflammation in the IPF population [32]. Nagao et al [32 ]demonstrated that the UIP histology showed a greater paucity of bronchoalveolar lavage fluid lymphocytosis in the IPF patient group than in the UIP patient group with associated collagen vascular disease. In addition, most IPF patients in our group presented at later stages of the disease with advanced fibrotic changes, whereas ground-glass opacity was expected to be minimal.…”
Section: Discussionmentioning
confidence: 99%
“…The BAL findings are also somewhat different from IPF. The general pattern is increased neutrophils, with or without eosinophils, but increased lymphocytes are more commonly seen than in IPF [31]. In general, BAL seems to have a limited value in the diagnosis of CVD affecting the lungs because the BAL profile is very nonspecific.…”
Section: Collagen Vascular Diseasementioning
confidence: 99%